Enantioselective total syntheses of (−)-clavaminol A and deacetyl (+)-clavaminol H. Issue 17 (2nd September 2018) - Pandey, Rachana; Gehlawat, Anju; Prakash, Ranjana; Kumar Pandey, Satyendra
Abstract: An efficient enantioselective approach to the syntheses of (−)-clavaminol A and deacetyl (+)-clavaminol H is presented, starting from n -decanol. The synthesis features Sharpless asymmetric dihydroxylation (AD), regioselective epoxide formation/opening and α -tosylation as key steps. Graphical Abstract: